1984
DOI: 10.1042/bj2200693
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine metabolism in vitamin-B-6-deficient rat liver after tryptophan injection

Abstract: Tryptophan contents of liver, serum and kidney were determined in normal and vitamin-B-6-deficient rats after tryptophan injection. Tryptophan contents of normal and B-6-deficient liver were different, but not those in serum and kidney. Both kynurenine and 3-hydroxykynurenine accumulated in B-6-deficient liver more than in the normal. The 3-hydroxykynurenine contents after tryptophan injection (30 mg/100 g body wt.) increased to 1380 nmol/g of liver at 1-1.5 h, a value sufficient to produce xanthurenate, in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Stanley et al (25) reported that the control strength of kynureninase in B6-deficient liver cell was higher than that of tryptophan 2, 3-dioxygenase . As we showed previously, excess tryptophan injection to B6-deficient rat led to the accumulation of a large quantity of kynurenine and 3-hydroxykynurenine in liver (6) . These indicated that liver metabolized tryptophan extremely and released its metabolites , especially kynurenine and 3-hydroxykynurenine, to the blood.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Stanley et al (25) reported that the control strength of kynureninase in B6-deficient liver cell was higher than that of tryptophan 2, 3-dioxygenase . As we showed previously, excess tryptophan injection to B6-deficient rat led to the accumulation of a large quantity of kynurenine and 3-hydroxykynurenine in liver (6) . These indicated that liver metabolized tryptophan extremely and released its metabolites , especially kynurenine and 3-hydroxykynurenine, to the blood.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, these seemed to cause the apparent increase of saturation level with pyridoxal phosphate in B6-deficient kidney after tryptophan injection. Moreover, the effects of tryptophan adminis tration on the activities of normal kidney kynureninase and B6-deficient kidney mitochondrial kynurenine aminotransferase were different from those in the liver (6). Although the reason for these differences is unknown, the responsiveness to tryptophan injection seemed to be different between liver and kidney.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations